The automotive industry: The potential for sustainable regional cooperation - Gordon, Joshua (School of Economics, 2022)
Regional integration has widely been accepted as a means for industrialisation in Africa, particularly in Sub-Saharan Africa (SSA). However, the standard approaches used by economists to assess the feasibility of regional cooperation fall short. The reciprocal relationship between market forces and politico-social institutions is too often assumed away. Further, the automotive industry has been acknowledged as an important sector that has the potential to drive industrialisation in SSA. However, in order for the automotive sector to be sustainable, regional cooperation is important. To this end, this paper attempts to assess whether regional cooperation in the automotive sector is feasible. The automotive industry is used as a vehicle to assess whether the demand and supply side conditions, set out by the dynamic model, are satisfied. It is concluded that, in Sub-Saharan Africa, there are regional actors who stand to gain from institutional reform, enhancing the prospects of sustained regional cooperation in the automotive industry. Further, it is concluded that, while the supply side conditions are unambiguously satisfied currently, there is potential for clear regional leaders to emerge in the future.